Neural relapse in multibacillary leprosy 6 years after end of treatment Recidiva neural em hanseníase multibacilar após 6 anos de tratamento - Leandra Oliveira Teixeira; Carlos Maximiliano Gaspar Carvalho Heil Silva; Hélcio Takeshi Akamatsu; Jaison Antônio Barreto; Cleverson Teixeira Soares (Sociedade Brasileira de Dermatologia, 2012)
This article presents a case of relapse, with isolated neural manifestation, in a multibacillary patient previously treated with multidrug therapy for multibacillary leprosy (24 doses). The patient returned to the service six years after the end of treatment, with pain in hands and legs. He was investigated, and the serological monitoring showed an important increase in anti-phenolic glycolipid serum levels. A neural recurrence was suspected, since the patient had no new skin lesions. A new biopsy in the right ulnar nerve showed a bacilloscopy of 2 +, compatible with relapse. This is a literature review of the etiological, clinical, propedeutical and diagnostic aspects of this situation so poorly understood. O presente artigo relata um caso de recidiva, com manifestação neural isolada, em paciente multibacilar previamente tratado com poliquimioterapia para multibacilar 24 doses. O paciente retorna ao serviço, seis anos depois do fim do tratamento, com dores em mãos e pernas. Na investigação, o acompanhamento da sorologia anti-glicolipídeo fenólico 1 demonstrou aumento importante dos níveis séricos, e foi aventada a hipótese de recidiva neural, já que o paciente não apresentava lesões cutâneas novas. Uma nova biópsia, em nervo ulnar direito, demonstrou baciloscopia de 2+, compatível com recidiva. Faz-se revisão da literatura sobre aspectos etiológicos, clínicos, propedêuticos e diagnósticos dessa situação tão pouco compreendida.